2013
DOI: 10.1007/s00268-013-2133-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life (QoL) in Patients With Benign Thyroid Goiters (Pre‐ and Post‐Thyroidectomy): A Prospective Study

Abstract: Patients with benign goiters experience significant improvement in QoL after thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
72
6
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 35 publications
11
72
6
2
Order By: Relevance
“…Another important issue that could modify/influence both surgeon and patient choice in favor of a surgical option is the assessment of the QoL after thyroidectomy. Prior studies indicated that surgery extent does not influence the QoL [38] and the specific symptom Btiredness^remains one of the most affected domains [39][40][41] after thyroidectomy. It should be noted that in these studies both TT and HT are considered together.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important issue that could modify/influence both surgeon and patient choice in favor of a surgical option is the assessment of the QoL after thyroidectomy. Prior studies indicated that surgery extent does not influence the QoL [38] and the specific symptom Btiredness^remains one of the most affected domains [39][40][41] after thyroidectomy. It should be noted that in these studies both TT and HT are considered together.…”
Section: Discussionmentioning
confidence: 99%
“…One study highlighted the psychological changes rather than appearance or worsening of the tiredness or asthenia [11]. Another study showed the advantages of thyroidectomy in reducing post-operative fatigue by evaluating a cohort of patients with various hormone levels [8]. A recent study [12] reported that TT is frequently accompanied by chronic low-moderate asthenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast et al (2014) found that the majority of patients treated with rhTSH for goitre reported an improvement in symptoms on the specific ThyPRO scale concerning goitre, and that the improvement persisted at least up to the 36 th month [19]. Moreover, according to studies conducted by two groups of surgeons on patients who had undergone thyroidectomy for goitre, QoL improved significantly after surgery, whether total thyroidectomy or hemithyroidectomy had been performed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Понятно, что значительная часть пациентов, страдающих патологией щитовидной железы, нуж-даются в хирургическом лечении, и ввиду большой распространенности данной патологии важнейшей задачей современной хирургии становится улучше-ние качества жизни больных в послеоперационном периоде [5][6][7][8]. Очевидно, что основное внимание в этом вопросе приковано к предотвращению раз-вития таких тяжелых осложнений, как параличи гортани и послеоперационный гипопаратиреоз, ко-торые могут привести к инвалидизации пациента.…”
unclassified